Review of the Philippine taxa formerly assigned to the genus Amphicnemis Selys, II. Genus Sangabasis with descriptions of eight new species (Odonata: Coenagrionidae) - Villanueva, R. J.t.; Dow, R. A. (Zootaxa, 2014)
The Philippine genus Sangabasis Villanueva is reviewed. Eight new species are described: S. bukid sp. nov., S. bulba sp. nov., S. cahilogi sp. nov., S. carmelae sp. nov., S. feliculoi sp. nov., S. hamis sp. nov., S. janvantoli sp. nov., and S. zamboanga sp. nov.